A plant pathogenic fungus eliciting necrosis (leaf spot) against Exbucklandia populnea (R.Br. ex Griff.) R.W.Br. (GEROK) at Forest Nursery Terla B - Kikuchi, Tatsuro (2019)
Exbucklandia populnea is an important species for a restoration programme in Cameron Highlands as it is a common pioneer tree in Cameron Highlands. However, necrotic disease was observed and killed a lot of seedlings of E. populnea at Forest Nursery Terla B, which is the only nursery for the restoration in Cameron Highlands. Further spread of the disease is considered to be able to decrease the supply of seedlings of E. populnea because the germination rate of the seeds is low, and the seedlings grow slowly. Therefore, the purpose of this study is to determine the causal agent of the disease and estimate the impact in the nursery. From a survey at the nursery, nearly 30 % of E. populnea seedlings showed necrotic disease, which made it the most dominant disease in the nursery, and the necrotic symptom was categorized into two sub-symptoms: TS (small brown spots) on young leaves and TB (big brown spots) on both old and young leaves. The symptomatic leaves of E. populnea were collected at the nursery, and the necrotic tissues were cut into small pieces. The pieces and the spores on the spots were placed onto potato dextrose agar media and incubated at room temperature (27-30 °C). From both of TS and TB symptomatic leaves a grey colonial fungus named T1 was isolated. T1 had identical spores and hyphae that were confirmed on both TS and TB symptomatic leaves. Thus, T1 was suspected as the causal agent of both of the types of leaf spot diseases. All strains of T1 were identified as Botrytis cinerea by DNA sequencing of ITS region. The fungus is notorious for causing necrotic diseases on plants in nurseries. Mycelial suspension and mycelial plugs were used as inoculums for the pathogenic tests. During the tests, TB symptom was confirmed on the inoculated leaves, but TS symptom did not occur. Thereby, it was not fully confirmed in this study that TS symptom was caused by B. cinerea, although this symptom was highly likely caused by B. cinerea. TS symptom was considered to be not simply caused by surface inoculation and might involve physiological change of B. cinerea from endophytic to necrotrophic life style as previous research shows. Further research about the relationship between E. populnea and B. cinerea would help to find specific measures to control the necrotic diseases.